E2F4-RB and E2F4-p107 complexes suppress gene expression by transforming growth factor β through E2F binding sites - Li, Jian-Ming (The National Academy of Sciences of the USA, 1997)
Transforming growth factor β (TGF-β) causes growth arrest in most cell types. TGF-β induces hypophosphorylation of retinoblastoma susceptibility gene 1 product (RB), which sequesters E2F factors needed for progression into S phase of the cell cycle, thereby leading to cell cycle arrest at G(1). It is possible, however, that the E2F-RB complex induced by TGF-β may bind to E2F sites and suppress expression of specific genes whose promoters contain E2F binding sites. We show here that TGF-β treatment of HaCaT cells induced the formation of E2F4-RB and E2F4-p107 complexes, which are capable of binding to E2F sites. Disruption of their binding to DNA with mutation in the E2F sites did not change the expression from promoters of E2F1, B-myb, or HsORC1 genes in cycling HaCaT cells. However, the same mutation stimulated 5- to 6-fold higher expression from all three promoters in cells treated with TGF-β. These results suggest that E2F binding sites play an essential role in the transcription repression of these genes under TGF-β treatment. Consistent with their repression of TGF-β-induced gene expression, introduction of E2F sites into the promoter of cyclin-dependent kinase inhibitor p15(INK4B) gene effectively inhibited its induction by TGF-β. Experiments utilizing Gal4-RB and Gal4-p107 chimeric constructs demonstrated that either RB or p107 could directly repress TGF-β induction of p15(INK4B) gene when tethered to p15(INK4B) promoter through Gal4 DNA binding sites. Therefore, E2F functions to bring RB and p107 to E2F sites and represses gene expression by TGF-β. These results define a specific function for E2F4-RB and E2F4-p107 complexes in gene repression under TGF-β treatment, which may constitute an integral part of the TGF-β-induced growth arrest program.